Life Relational Paradigm (LRP) in the face of human and environmental emergencies: remodelling human relations in the world - Medina, Alice Maria Corrêa (Revista Brasileira de Educação Ambiental (RevBEA), 2020)
This article sets forth the - Life Relational Paradigm (LRP) as a multiplier of the production of values originated from the promotion and maintenance of life. The concept of LRP is based on the convergence of the human and environmental dimensions, considering values, attitudes, and behaviours as consequences of experienced relations. LRP aims at promoting and spreading thoughts and actions rooted in values which favour life by producing environmental principles and meanings and therefore fostering more responsible and engaged interactions, which are beyond the notion of preservation and as a new way to live in this world.